2023
DOI: 10.1371/journal.pone.0280981
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic malaria infection by microscopy and its determinants among residents of Ido-Ekiti, Southwestern Nigeria

Abstract: Background Asymptomatic malaria infections have received less attention than symptomatic malaria infections in major studies. Few epidemiological studies on asymptomatic malaria infections have often focused on pregnant women and children under-five years of age as the most vulnerable groups. However, there is limitation on data regarding asymptomatic infections among the old adult populations, particularly in the study area. Therefore, this study determined the prevalence of asymptomatic malaria infection by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Using multivariate regression for factors that were significantly associated with malaria infection in this study, respondents who had no formal education were 3.403 times more likely to increase the odds of malaria infection as compared to those who had formal education. This was similar to cross sectional studies conducted in Ibadan Southwestern Nigeria [11], Kano Northwestern Nigeria [9], and Kenya [35], which showed that level of education significantly influences the knowledge, attitude, and practice of people in various malaria interventions, treatment, and control [9,11,33,35].…”
Section: Plos Onesupporting
confidence: 84%
See 1 more Smart Citation
“…Using multivariate regression for factors that were significantly associated with malaria infection in this study, respondents who had no formal education were 3.403 times more likely to increase the odds of malaria infection as compared to those who had formal education. This was similar to cross sectional studies conducted in Ibadan Southwestern Nigeria [11], Kano Northwestern Nigeria [9], and Kenya [35], which showed that level of education significantly influences the knowledge, attitude, and practice of people in various malaria interventions, treatment, and control [9,11,33,35].…”
Section: Plos Onesupporting
confidence: 84%
“…This is comparable to cross sectional study conducted in other malaria endemic setting [14]. This finding was not surprised given the fact that P. falciparum is the dominant Plasmodium species in Southwestern Nigeria [30,33], Africa [34], and 99.7% estimated malaria cases of P. falciparum have been documented from WHO African regions [1]. It is responsible for the reported high morbidity and mortality among children, especially in sub-Sahara Africa countries.…”
Section: Plos Onesupporting
confidence: 78%
“…This is recognised as an obstacle in malaria elimination [ 141 , 142 ]. Asymptomatic malaria infections have received less research attention than symptomatic infections in major studies [ 143 , 144 ] and even when developing mathematical models. Only a few models have explicitly considered asymptomatic infections [ 55 , 72 , 74 , 87 ].…”
Section: Search Resultsmentioning
confidence: 99%
“…The World Health Organization's current guidelines focus on "test, treat, and trace" strategies of symptomatic individuals, complemented by preventive efforts such as vector control and chemoprophylaxis for high-risk groups (2,3). However, there is growing recognition that many individuals infected with malaria may not display overt symptoms, due to immune protection from previous exposures and other factors, but yet may still contribute to overall disease transmission (4)(5)(6). The extent to which these asymptomatic infections exist in a population may help to determine the effectiveness of existing control efforts.…”
Section: Introductionmentioning
confidence: 99%